La lunga ombra dell’orientalismo tra studi africani e studi berberi in Italia - Merolla, Daniela (Incontri. Rivista europea di studi italiani, 2013)
Present Italian studies on Africa go beyond regional and disciplinary divides of the past. The trend is towards a positive transgression of previous boundaries, and scholars have shifted attention from the disciplinary approach to the transdisciplinaryand inter-disciplinary research. However, elements and trends of the past still influence the relationship between Berber literary studies and African literary studies in Italy. This paper offers a first reflection on the long-term relationships between Africanist studies and studies on Berber literature by taking into account conjunctures and disjunctures in the complex construction of thegeographical and cultural notions of (and divide between) ‘Africa’ and ‘North Africa’.The aim is to understand specificity and continuity of the relationship betweenBerber studies and Africanist studies in Italy when compared to international studies.Looking at the Italian studies of Berber literature, one finds a strong influence of the linguistic and philological approaches. Moreover, one recognizes the tendency of thestudies to look ‘East’ rather than ‘South’ in establishing their cultural and political framework of reference. On the other hand, studies that give attention to new developments in Berber written literature spring usually from African ’post-colonial’ literary studies. However, the situation is also evolving in the specific field of Italian Berber studies.